Big Bite Burger / Nurul Khairunnisa Mustafar ... [et al.] - Mustafar, Nurul Khairunnisa; A. Rahman, Nurul Murni; Marjookee, Suziliyanti; Mohd Haniff, Nurulliyana; Abd Halim, Uffairah (Faculty of Hotel and Tourism Management, 2006)
Nowadays in Malaysia there are many entrepreneurs involves in business especially in food manufacturing. Since there are many women who are working and did not have time to cook for their family, BIG BITE BURGER has taken this advantage to open a business dealing with food which can give a good profit. BIG BITE BURGER is the inspirations of five women which have qualifications in food service management. We have chosen this name because we produce a bigger burger patty compared to our competitors, which we believe will satisfy our customers. With only a few numbers of companies which produce the burger patty based on seafood and vegetables have inspired us to create something new to expand our market. Our main specialties are the Black Pepper Beef, the Chicken Mushroom, the Vegan Veggie Burger and Crab Delight. We also sell these burger patties in our shop besides distributing it to the supermarkets.